How do basin committees deal with water crises. reflections for adaptive water governance from south america - Micaela Trimble, Tomás Olivier, Lidiane Anjos, Natalia Dias Tadeu, Gabriel Giordano, Lara Mac Donnell, Rosana Laura, Franco Salvadores, Igor Santana-Chaves, Pedro Torres, Miguel Pascual, Pedro Jacobi, Néstor Mazzeo, Cristina Zurbriggen, Lydia Garrido, Esteban Jobbágy, Claudia Pahl-Wostl (My University, 2022)
Adaptive water governance involves collaboration among multiple actors, social learning, and flexibility to deal with shocks and surprises. Crises thus become a useful context to assess how the institutional arrangements contribute to adaptation. However, an important part of the specialized literature has focused on these issues as they occur in highly institutionalized settings in the Global North. This paper, instead, analyzes basin organizations in settings with variable degrees of institutionalization in South America. The objective is to analyze the actions (or lack thereof) conducted or encouraged by basin committees in watersheds of Argentina, Brazil, and Uruguay, in the face of water crises. We analyze three case studies, involving basin committees that faced different water crises (all affecting drinking water supply) at different scales: (1) Chubut River Basin committee and a turbidity crisis in the Lower Valley in 2017 (Chubut, Argentina), (2) Piracicaba-Capivari-Jundiaí (PCJ) River Basins committee and a drought that occurred in 2014&ndash2015 (São Paulo, Brazil), and (3) Laguna del Cisne Basin commission and a crisis associated with a failure in the water treatment operation in 2019 (Canelones, Uruguay). In each case, we analyze the institutional design of the committee and the actions (or lack thereof) undertaken regarding the crisis, including the perceptions of key stakeholders of those actions. Findings showed that stakeholders tend to act and communicate through fast channels when water crises occur, referring to basin committees only for technical and additional support (Brazil), information sharing (Uruguay), or not convening the committee at all (Argentina). Our cases in South American countries with different contexts provided empirical evidence of the barriers that basin committees face as political&ndashinstitutional frameworks to foster adaptive water governance (e.g., limited stability, centralization, lack of leadership).
Keywords: adaptive governance; centralization; participation; river basin organizations; watersheds